ANALISIS PENERAPAN METODE PELATIHAN DAN PENGEMBANGAN KARYAWAN UNTUK MENINGKATKAN KOMPETENSI PEGAWAI DPMPTSP KARAWANG - Melanda Wulandari; Dedi Mulyadi; Sungkono Sungkono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study analyzes the implementation of employee training and development methods at the Investment and One-Stop Integrated Services Office (DPMPTSP) in Karawang to enhance employee competence. Using a qualitative approach, this research involved interviews and observations of 3 DPMPTSP Karawang employees. The results show that DPMPTSP Karawang has implemented various training methods, including classroom training, e-learning, and on-the-job training. The majority of respondents reported significant improvements in technical and soft skills. However, several challenges were identified, such as time constraints and difficulties in applying new knowledge. Nevertheless, the training programs positively impacted employee performance, with increased efficiency and work motivation. This study recommends adjustments in program design and implementation, including improving evaluation systems and adopting more flexible learning methods to enhance the effectiveness of employee training and development programs at DPMPTSP Karawang.